Effects of Periodontal Endoscopy-Assisted Nonsurgical Treatment of Periodontitis: Four-Month Results of a Randomized Controlled Split-Mouth Pilot Study - Christian Graetz; Johanna Sentker; Miriam Cyris; Susanne Schorr; Claudia Springer; Karim M. Fawzy El-Sayed (International Journal of Dentistry)
Objective. Although the therapeutic effects of nonsurgical periodontal therapy (NSPT) are well established, the clinical benefits of the additional use of periodontal endoscopy (PE) remain controversial. Therefore, this randomized controlled split-mouth pilot study evaluated the effect of NSPT using PE versus NSPT without nPE on bleeding on probing (BOP) in sites with probing depth (PD)≥4 mm (primary outcome), PD, clinical attachment level (CAL), number of hard deposits (HDs), and treatment time per tooth (TrT). Methods. Two calibrated operators performed NSPT in twenty periodontitis patients, randomized into two quadrants for PE or nPE treatment. BOP, PD, and CAL were recorded at the first visit for NSPT (T0) and during reevaluation (T1: mean (SD) 119.7 (24.6) days after T0). The average TrT and the number of sites with HDs were documented at T0. Results. For BOP, no significant differences were found at the patient’s level (10/10 (male/female); aged 54.3 (10.9) years) neither within or between the groups. At tooth surface level, a lower number of surfaces with BOP p=0.026 was observed in nPE. CAL and PD improved significantly during NSPT in both groups p≤0.001, with higher PD reduction p<0.001 and CAL gain p<0.001 in nPE. There are significantly longer TrT p<0.001 and more surfaces with subgingival HDs evident in PE at T0 p=0.001. Conclusion. Whereas subgingival HDs can be visually detected with PE during NSPT, no additional clinical benefits regarding BOP, PD, or CAL were notable compared to conventional systematic periodontal instrumentation. Additionally, PE-assisted NSPT required a longer treatment time.